2014
DOI: 10.1007/s00464-014-3480-3
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted laparoscopy for deep infiltrating endometriosis: international multicentric retrospective study

Abstract: This study analyzed the largest series of robot-assisted laparoscopies for deep infiltrating endometriosis published in the literature. No increase in surgical time, blood loss, or intra- or postoperative complications was observed. The interest in robot-assisted laparoscopy for deep infiltrating endometriosis seems to be promising.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 29 publications
3
40
1
6
Order By: Relevance
“…Collinet et al ont publié la plus grande sé rie de femmes (dont certaines font partie de cette é tude) opé ré es en chirurgie laparoscopique robot-assisté e pour de l'endomé triose profonde [9]. Cette sé rie met en é vidence que la chirurgie laparoscopique robot-assisté e, avec les avantages qu'elle apporte, n'augmente pas la morbidité peropé ratoire.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Collinet et al ont publié la plus grande sé rie de femmes (dont certaines font partie de cette é tude) opé ré es en chirurgie laparoscopique robot-assisté e pour de l'endomé triose profonde [9]. Cette sé rie met en é vidence que la chirurgie laparoscopique robot-assisté e, avec les avantages qu'elle apporte, n'augmente pas la morbidité peropé ratoire.…”
Section: Discussionunclassified
“…Collinet et al, avec leur sé rie multicentrique de 164 femmes, ont montré que la chirurgie laparoscopique robot-assisté e é tait une voie d'abord prometteuse pour la prise en charge de d'endomé triose sous-pé ritoné ale profonde [9]. La morbidité du shaving et de la ré section digestive en chirurgie laparoscopique robot-assisté e a é té comparé e par Ercoli et al dans une sé rie de 22 femmes parmi lesquelles douze ont eu une ré section digestive et dix ont eu un shaving [10].…”
Section: Introductionunclassified
“…This technique when compared to the standard technique appears to be associated with significantly less bladder/bowel and sexual dysfunction. 40,41 Thus there is still no definitive consensus on which approach is the "best" technique to treat bowel endometriosis; ultimately the aim of treating DIE affecting the bowel should focus on the long-term resolution of bowel symptoms with the fewest complications. Detailed counseling and a multidisciplinary approach is key.…”
Section: Bowel Endometriosismentioning
confidence: 99%
“…The first 3D laparoscopy systems have been introduced into clinical practice for about 30 years, while the Da Vinci® system (Intuitive Surgical Inc, Sunnyvale CA, USA) was authorized for gynecologic surgery in April 2005 and its three-dimensional (3D) vision and a higher degree of forceps freedom had provided advantages of minimally invasive surgery 1-4. Some previous studies showed that robot-assisted surgery in benign gynecological diseases had no obvious advantage 5-7.…”
Section: Introductionmentioning
confidence: 99%